The Role of Visual Effects: An E-Commerce Perspective on the Nigerian Arts and Crafts - Siyanbola, Afeez Babatunde; Oyinloye, Michael Abiodun; Oladesu, Johnson O.; Adeyemi, Adedola Olayinka (SCHOLARS: Journal of Arts & Humanities, 2021)
This paper explores the role of colour and visual weight in developing craftsential e-commerce platform for enhancing the patronage of Nigerian arts and crafts. The paper articulates the impressive embrace of e-commerce as a viable alternative to physical retail shopping. The graphic user interface of craftsential e-commerce platform developed to exclusively promote arts and crafts was explored vis-à-vis colours and visual weight of the sites visual indicators and icons. The study administered the questionnaires on three hundred and thirteen respondents constituting of e-commerce users, graphic designers/artists and programmers. Statistical Package of Social Science (SPSS) was used to analyze the results. Findings revealed that the colourful graphic user interface (look and feel) of e-commerce stores facilitates immersive shopping experience online and concise visual weight and direction in the atmospheric cue of e-commerce stores, enhancing navigation. The study recommended that makers and sellers of Nigerian crafts should explore the limitless opportunities offered by e-commerce to leverage an impressive market embrace of their products that transcend their geographical constrains. In addition, to stimulate shopper’s interest, the images of retailed craft works displayed on e-commerce stores should reflect the product merchandizing, clarity and attractiveness that enhance shopping experience.